Teacher and School Factors Predicting Learning Outcomes in Yoruba Orthography among Senior Secondary School Students in Oyo State, Nigeria - Makinde, Solomon Olanrewaju; Adetokun, Rauf Babafemi (International Journal of Social Learning (IJSL), 2022)
This study investigated teachers' job satisfaction, teachers' content knowledge, school type, and location as predictors of students' learning outcomes in Yoruba orthography. The study adopted a descriptive survey design of correlational type.  Ten teachers and 300 Yoruba students were randomly selected from ten (10) Senior Secondary Schools in Akinyele Local Government, Ibadan, with equal representation of rural and urban areas. Four instruments were used for data collection andanalyzed using descriptive and inferential statistics. Findings showed that students'attitude to Yoruba orthography significantly positively correlated with teacherjob satisfaction, teacher content knowledge, and school types, while school location did not. Teachers'job satisfaction, content knowledge, school location, and school types were significant to students' achievement.The composite contribution of the independent variables on students' attitudes and achievement in Yoruba orthography remained significant.Teachers' job satisfaction potentiatedto predicting students' learning attitudeand achievement in Yoruba orthography.